Two new species of Dermoloma from India - Raj, K. N. Anil; Latha, K. P. Deepna; Paramban, Raihana; Manimohan, Patinjareveettil (Phytotaxa, 2014)
Two new species of Dermoloma, Dermoloma indicum and Dermoloma keralense, are documented from Kerala State, India, based on morphology. Comprehensive descriptions, photographs, and comparison with phenetically similar species are provided.